1996
DOI: 10.1152/jappl.1996.80.4.1331
|View full text |Cite
|
Sign up to set email alerts
|

Heart, liver, and skeletal muscle myeloperoxidase activity during exercise

Abstract: The purpose of this study was to determine whether contractile activity associated with running exercise was a prerequisite for neutrophil infiltration into rat tissues. H2O2-dependent myeloperoxidase (MPO) activity for rat (n = 8) liver, heart, and gastrocnemius muscles was assayed after 58 +/- 11 min of running to voluntary exhaustion (25 m/min; 0% grade). MPO activity values measured with 0.6 mM H2O2 were 0.988 +/- 0.331 (SD) U/g (skeletal muscle), 1.563 +/- 0.303 U/g (heart), and 1.652 +/- 0.510 U/g (liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 0 publications
3
74
1
5
Order By: Relevance
“…The present study demonstrated that Iba1-positive macrophages are the major inflammatory cells in skeletal muscle lesions that positively correlate with the number of regenerating myofibers, whereas Gr1-positive granulocytes, mainly neutrophils, negatively correlate with regenerated myofibers in mdx mice. After muscle injury caused by trauma such as extensive physical activity, or by innate genetic defects, inflammatory cells such as neutrophils and macrophages infiltrate into the lesions (Belcastro et al 1996). Necrosis of myofibers is the initial event in skeletal muscle degeneration, accompanied by the activation of mononucleated cells, principally inflammatory and myogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that Iba1-positive macrophages are the major inflammatory cells in skeletal muscle lesions that positively correlate with the number of regenerating myofibers, whereas Gr1-positive granulocytes, mainly neutrophils, negatively correlate with regenerated myofibers in mdx mice. After muscle injury caused by trauma such as extensive physical activity, or by innate genetic defects, inflammatory cells such as neutrophils and macrophages infiltrate into the lesions (Belcastro et al 1996). Necrosis of myofibers is the initial event in skeletal muscle degeneration, accompanied by the activation of mononucleated cells, principally inflammatory and myogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CD43 has been used as an indicator on neutrophil infiltration of skeletal muscle following damage (Tidball et al, 1999). Muscle MPO activity also has been commonly used as a quantitative marker of muscle neutrophil infiltration following exercise or ischemia induced damage (i.e., Squadrito et al, 1997;Belcastro et al, 1996;Tiidus et al, 2001). Our previous study found no elevation in MPO activities in soleus muscle at two hours after a two-hour ischemic period in ovariectomized or gonad-intact female rats (Stupka and Tiidus, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…All muscle samples (PL, WG, RG) were analyzed for myeloperoxidase (MPO), glucose-6-phosphate dehydrogenase (G6PD) and bglucuronidase (bGLU) activites. Muscle MPO activity is a marker of leukocyte (primarily neutrophil) infiltration (Belcastro et al, 1996). Muscle MPO activity was determined spectrophotometrically from homogenates using the method of Smith and colleagues (1989).…”
Section: Blood and Tissue Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been well documented that the MPO activity becomes elevated in response to intensive exercise both in humans and animals [11,52,53]. However, it should be stressed that the main source of the circulating MPO is its release from the neutrophils, whose count in the blood is stimulated in response to exercise [54,56].…”
Section: Paraoxonase 1 Myeloperoxidase and Physical Activitymentioning
confidence: 99%